Relationship between reproductive risk factors, tumor characteristics and survival in breast cancer molecular groups - Zaha, Dana Carmen; Cioara, Felicia; Suciu, Ramona; Daina, Lucia (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Introduction. Breast cancer may be classified into distinct molecular subtypes based on gene expression profiling or immunohistochemical methods. These molecular subtypes are prognostically significant, but their etiologic profiles have not been well established. Our study investigates the relationships between menstrual factors: age of menarche/menopause, irregular/regular menstruation, parity and use of oral contraceptives, tumor characteristics, survival related by the molecular subtypes. Methods. This study was performed on a group of 173 of patients diagnosticated with breast cancer at The Municipal Clinical Hospital of Timisoara, data being obtained from the medical records of the patients and through a questionnaire sent by post. Molecular classification was made by immunohistochemistry using a panel of four markers: estrogen receptor, progesterone receptor, human epidermal growth factor receptor 2 and CK 5/6. All reproductive factors were analyzed in relation to molecular classes and survival. Results. Younger age at menarche was significantly associated with HER2 and triple-negative subtypes and survival rates were the poorest in women from these groups. The patients with luminal subtype tumors were mostly multiparous whereas the patients with HER2 and triple-negative tumors presented low parity. Conclusions. From the studied hormonal and menstrual risk factors menopausal status, age at menarche and menopause, oral contraceptives use, parity and family history of breast cancer showed significant trends among tumor subtype and they have a significant impact on molecular breast cancer groups regarding prognosis and survival.